Lenvatinib plus Pembrolizumab or Everolimus for Advanced Renal Cell Carcinoma - Motzer, Robert; Alekseev, Boris; Rha, Sun-Young; Porta, Camillo; Eto, Masatoshi; Powles, Thomas; Grünwald, Viktor; Hutson, Thomas E; Kopyltsov, Evgeny; Méndez-Vidal, María J; Kozlov, Vadim; Alyasova, Anna; et al. (The New England journal of medicine, 2021)
BACKGROUND: Lenvatinib in combination with pembrolizumab or everolimus has activity against advanced renal cell carcinoma. The efficacy of these regimens as compared with that of sunitinib is unclear. METHODS: In this phase 3 trial, we randomly assigned (in a 1:1:1 ratio) patients with advanced renal cell carcinoma and no previous systemic therapy to receive lenvatinib (20 mg orally once daily) plus pembrolizumab (200 mg intravenously once every 3 weeks), lenvatinib (18 mg orally once daily) plus everolimus (5 mg orally once daily), or sunitinib (50 mg orally once daily, alternating 4 weeks receiving treatment and 2 weeks without treatment). The primary end point was progression-free survival, as assessed by an independent review committee in accordance with Response Evaluation Criteria in Solid Tumors, version 1.1. Overall survival and safety were also evaluated. RESULTS: A total of 1069 patients were randomly assigned to receive lenvatinib plus pembrolizumab (355 patients), lenvatinib plus everolimus (357), or sunitinib (357). Progression-free survival was longer with lenvatinib plus pembrolizumab than with sunitinib (median, 23.9 vs. 9.2 months; hazard ratio for disease progression or death, 0.39; 95% confidence interval [CI], 0.32 to 0.49; P<0.001) and was longer with lenvatinib plus everolimus than with sunitinib (median, 14.7 vs. 9.2 months; hazard ratio, 0.65; 95% CI, 0.53 to 0.80; P<0.001). Overall survival was longer with lenvatinib plus pembrolizumab than with sunitinib (hazard ratio for death, 0.66; 95% CI, 0.49 to 0.88; P = 0.005) but was not longer with lenvatinib plus everolimus than with sunitinib (hazard ratio, 1.15; 95% CI, 0.88 to 1.50; P = 0.30). Grade 3 or higher adverse events emerged or worsened during treatment in 82.4% of the patients who received lenvatinib plus pembrolizumab, 83.1% of those who received lenvatinib plus everolimus, and 71.8% of those who received sunitinib. Grade 3 or higher adverse events occurring in at least 10% of the patients in any group included hypertension, diarrhea, and elevated lipase levels. CONCLUSIONS: Lenvatinib plus pembrolizumab was associated with significantly longer progression-free survival and overall survival than sunitinib. (Funded by Eisai and Merck Sharp and Dohme; CLEAR ClinicalTrials.gov number, NCT02811861.).
Keywords: nádory ledvin; Humans; inhibitory proteinkinas; lidé středního věku; analýza přežití; sunitinib; Female; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; Antineoplastic Agents; antigeny CD279; Quinolines; senioři; lidé; humanizované monoklonální protilátky; doba přežití bez progrese choroby; Survival Analysis; Phenylurea Compounds; Adult; Protein Kinase Inhibitors; Antibodies, Monoclonal, Humanized; ženské pohlaví; Male; Middle Aged; Antineoplastic Combined Chemotherapy Protocols; everolimus; Aged, 80 and over; protinádorové látky; karcinom z renálních buněk; fenylmočovinové sloučeniny; senioři nad 80 let; Carcinoma, Renal Cell; Progression-Free Survival; Sunitinib; mužské pohlaví; Programmed Cell Death 1 Receptor; Everolimus; Kidney Neoplasms; chinoliny